Fintech and the Remaking of Financial Institutions - Hill, John (Academic Press, An imprint of Elsevier, 2018)
FinTech and the Remaking of Financial Institutions explores the transformative potential of new entrants and innovations on business models. In its survey and analysis of FinTech, the book addresses current and future states of money and banking. It provides broad contexts for understanding financial services, products, technology, regulations and social considerations. The book shows how FinTech has evolved and will drive the future of financial services, while other FinTech books concentrate on particular solutions and adopt perspectives of individual users, companies and investors. It sheds new light on disruption, innovation and opportunity by placing the financial technology revolution in larger contexts.